1999
DOI: 10.1021/bi991866o
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 50S Components Neighboring 23S rRNA Nucleotides A2448 and U2604 within the Peptidyl Transferase Center of Escherichia coli Ribosomes

Abstract: The 23S rRNA nucleotides 2604-12 and 2448-58 fall within the central loop of domain V, which forms a major part of the peptidyl transferase center of the ribosome. We report the synthesis of radioactive, photolabile 2'-O-methyloligoRNAs, PHONTs 1 and 2, complementary to these nucleotides and their exploitation in identifying 50S ribosomal subunit components neighboring their target sites. Photolysis of the 50S complex with PHONT 1, complementary to nts 2604-12, leads to target site-specific photoincorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…A second problem is the possibility of additional binding to secondary lower-affinity binding sites when excesses of oligonucleotide are used over 30 S subunits ( Figure 2B). Similar non-plateau binding curves have been reported in a previous study involving the use of excess photolabelled OMe oligonucleotides binding and cross-linking to the peptidyl transferase centre of 50 S subunits [18]. Thus filter binding appears to be inadequate for measurement of dissociation constants over a wide affinity range.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…A second problem is the possibility of additional binding to secondary lower-affinity binding sites when excesses of oligonucleotide are used over 30 S subunits ( Figure 2B). Similar non-plateau binding curves have been reported in a previous study involving the use of excess photolabelled OMe oligonucleotides binding and cross-linking to the peptidyl transferase centre of 50 S subunits [18]. Thus filter binding appears to be inadequate for measurement of dissociation constants over a wide affinity range.…”
Section: Discussionsupporting
confidence: 77%
“…Filter binding has been the primary method used to date for assessing the binding of oligonucleotides to 50 S ribosomal subunits [18,19]. We found that where excess oligonucleotide was used (Figure 2B), some of the 10-mer oligonucleotides did not reach a plateau in the graph where the level of filter retention was titrated against a fixed concentration of 30 S subunits, particularly for weaker interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In E. coli, L21 binds to 23S ribosomal RNA (Alexander and Cooperman, 1998;Vladimirov et al, 2000), which plays a direct role in protein synthesis (Samaha et al, 1995). Thus, nfd1 mutants are likely to be affected in protein synthesis within the mitochondrion.…”
Section: Discussionmentioning
confidence: 99%